Optoelectronic properties of In2S3 thin films measured using surface photovoltage spectroscopy. (10th April 2019) - Rasool, S; Saritha, K; Reddy, K T Ramakrishna; Bychto, L; Patryn, A; Maliński, M; Tivanov, M S; Gremenok, V F
Abstract: In recent years, In2 S3 thin films were widely used as buffer/window layer in thin film solar cells as an alternative to toxic CdS. In the present work, we demonstrate the potential of surface photovoltage spectroscopy for estimation of minority carrier diffusion length, band gap energy and refractive index of thermally evaporated In2 S3 thin films. The estimated minority carrier diffusion length of In2 S3 thin films from SPV measurements were 0.112 μ m and 0.052 μ m for films annealed at 250 and 300 °C respectively.